Utilization of almond residues - Chen, Paul; Yanling, Cheng; Shaobo, Deng; Xiangyang, Lin; Guangwei, Huang; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2010)
Abstract: Almond production generates millions of tons of residues in addition to almond nuts. Almond residues, including shells, hulls, pruning, leaves, skin and inedible kernel disposition, are good feedstocks for production of bioenergy and other valuable compounds. In this article, research on the utilization of almond residues as energy and non-energy feedstocks is reviewed. Technical options for converting almond residues to energy and other valuable products are discussed. Several commercial conversion technologies are examined. Needs for further research and development are recommended. Keywords: activated carbons, almond, anti-oxidants, bioenergy, biomass, biorefinery, gasification, heat, power, pyrolysis DOI: 10.3965/j.issn.1934-6344.2010.04.001-008 Citation: Paul Chen, Yanling Cheng, Shaobo Deng, Xiangyang Lin, Guangwei Huang, Roger Ruan. Utilization of almond residues. Int J Agric & Biol Eng, 2010; 3(4): 1<span style="line-height: 130%; font-family: